Antinociceptive activity of Melicope ptefolia ethanolic extract in experimental animals - Sulaiman, Mohd Roslan; Mohd Padzil, Azyyati; Shaari, Khozirah; Khalid, Syamimi; Shaik Mossadeq, Wan Mastura; Tengku Mohamad, Azam Shah; Ahmad, Syahida; Omar Farouk, Ahmad Akira; Israf Ali, Daud Ahmad; Lajis, Md. Nordin (Hindawi Publishing Corporation, 2010)
Melicope ptelefolia is a medicinal herb commonly used in Malaysia to treat fever, pain, wounds, and itches. The present study was conducted to evaluate the antinociceptive activity of the Melicope ptelefolia ethanolic extract (MPEE) using animal models of nociception. The antinociceptive activity of the extract was assessed using acetic acid-induced abdominal writhing, hot-plate, and formalin-induced paw licking tests. Oral administration of MPEE produced significant dose-dependent antinociceptive effects when tested in mice and rats using acetic acid-induced abdominal constriction test and on the second phase of the formalin-induced paw licking test, respectively. It was also demonstrated that MPEE had no effect on the response latency time to the heat stimulus in the thermal model of the hot-plate test. In addition, the antinociception produced by MPEE was not blocked by naloxone. Furthermore, oral administration of MPEE did not produce any effect in motor performance of the rota-rod test and in acute toxicity study no abnormal behaviors as well as mortality were observed up to a dose level of the extract of 5 g/kg. These results indicated that MPEE at all doses investigated which did not produce any sedative and toxic effects exerted pronounce antinociceptive activity that acts peripherally in experimental animals.